The impact of co‐teaching on the professional practices of veteran, novice, and potential science and mathematics teachers. (20th December 2021) - Sebald, Ann M.; Howe, John; Balgopal, Meena M.
Abstract: A university‐school district partnership program designed to increase recruitment and retention of science and mathematics teachers in schools identified as low performing by the school district, paired potential or novice teachers with veteran teachers in elementary or secondary schools. All participants received mentoring to build instructional practice in science and mathematics, enhance their science and mathematics skills, and increase the achievement of students in key areas of mathematics and science through co‐teaching practices. Pairs of veteran and novice/potential teachers co‐taught for a semester. All participants were interviewed during and after the co‐teaching experiences. We found that: (1) all participants perceived that shared collaborative practices were professionally important; (2) co‐teaching for both potential and novice teachers made them feel valued as educators; (3) both potential and novice teachers described plans to pursue or remain in teaching; and (4) veteran teachers described their perception of an expanded professional role as teacher recruiters. These findings have implications for the intervention of co‐teaching as a means to address teacher shortages, particularly in science and mathematics.